Work Beyond the Age of 50. What Role for Mental v.s. Physical Health? - Vincent Vandenberghe (Global Labor Organization (GLO), 2021)
This paper contributes to the literature on old employment barriers by exploring empirically the relative importance of mental v.s. physical health in determining work. It combines regression and variance decomposition analyses to quantify the respective role of mental v.s. physical health. The data used are from SHARE and inform in great detail on the health but also work status (i.e. employment and hours) of individuals aged 50+, interviewed between 2004 and 2017 in 21 European countries. The main result of the paper is that of the rather limited role of mental health | in comparison to physical health | in accounting for older individuals' work. The paper also shows that health (physical or mental) is much better at predicting old people's propensity to be in employment than the number of hours they work. Finally, the paper reveals that, in comparison to women, men's work is more driven by their health status.
Keywords: J22; I10; J26; J14; 330; Ageing; Work; Mental v.s. Physical Health; Regressions and Variance Decomposition